The Effects of Plasma Homocysteine Level on the Risk of Three Major Psychiatric Disorders: A Mendelian Randomization Study - Yu, Jing; Xue, Ranran; Wang, Qiuling; Yu, Hao; Liu, Xia (Frontiers in Psychiatry, 2022)
Background: Higher homocysteine (Hcy) level has been suggested to be associated with major psychiatric disorders (MPDs), such as schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD). We investigated the causal relationships between plasma Hcy level and MPDs risks using the Mendelian randomization (MR) method. Methods: We selected 18 loci associated with plasma Hcy level from a large-scale genome-wide association study (GWAS) as genetic instruments. Genetic associations with SCZ, MDD, BD and BD subtypes (BD-I and BD-II) were extracted from several GWAS datasets from the Psychiatric Genomics Consortium. We used the Generalized Summary-data-based Mendelian Randomization (GSMR) method to estimate the associations of genetically predicted plasma Hcy levels with MPDs risks. We also performed inverse variance-weighted (IVW) analysis to verify the GSMR results and used MR-Egger regression and leave-one-out analysis to test the assumptions for a valid MR analysis. Results: Genetically predicted plasma Hcy levels were associated with risks of SCZ (odds ratio [OR]=1.12, PGSMR =1.73×10-3) and BD-I (OR=1.14, PGSMR=5.23× 10−3) after Bonferroni correction. These associations were statistically significant when using IVW analysis (SCZ: OR=1.11, PIVW=2.74×10-3; BD-I: OR=1.13, PIVW =9.44× 10−3). Furthermore, no significant horizontal pleiotropy was found by sensitivity analysis, and leave-one-out analyses showed no specific SNP affected the overall estimate. However, genetically determined plasma Hcy levels were not causally associated with MDD, BD, or BD-II risks. Conclusion: Our results suggest that elevated plasma Hcy levels may increase the risk of SCZ or BD-I. Further randomized clinical trials are warranted to validate the MR findings in our study.